Positional Occlusion of an Interposition Vein Graft for Brachial Artery Reconstruction Following Open Elbow Dislocation in a Pediatric Patient: A Case Report. Issue 1 (14th January 2015) - Zhu, Andy F.; Seeley, Mark A.; Ozer, Kagan
Abstract : Case: : We present a case of positional occlusion of the brachial artery after open elbow dislocation and vein graft reconstruction in a pediatric patient. Two years after reconstruction, arterial Doppler studies demonstrated occlusion of the artery; however, an angiogram revealed a widely patent artery. Given the clinical findings of pain and cold intolerance, the patient underwent surgical exploration. Arterial occlusion was found to coincide with elbow flexion. The redundant segment of the basilic vein graft was resected and repaired end‐to‐end. Conclusions: : Vein graft reconstruction of the brachial artery should be checked for patency in flexion prior to closing the incision. Vein grafts with lengths in excess of a defect may kink in flexion due to redundant graft and the relatively thin walls of veins compared to arteries. This case report emphasizes that an understanding of routine tests is invaluable when eliciting the etiology of contradictory test results.